Sensory Evaluation and Protein Analysis of Catfish Stick - Melyani Rizky Ayundra Putri; Yuliana Arsil; Yessi Marlina; Roziana Roziana (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2022)
Increasing the protein content of the sticks can be done by substituting catfish as a protein source. The purpose of the study was to determine the level of preference and protein content of fish sticks with catfish flour substitution. This research is an experimental study with a completely randomized design (CRD), consisting of 4 kinds of ratios of wheat flour and catfish flour, namely 100%:0%, 80%:20%, 70%:30%, 60%:40%. The level of preference was carried out on 25 semi-trained panelists and protein content using the Kjeldahl Method. Data analysis using Oneway ANOVA and Duncan's advanced test. The most preferred taste and color were fish sticks with the addition of 40% catfish flour while the most preferred texture and the odor was 30% catfish flour. Substitution of catfish flour on catfish sticks had a significant effect on taste, color, texture, and aroma (p<0.05) and the highest protein content is stick with an additional 40% of catfish flour, with a protein content of 24.65%. It is recommended to carry out further research on the shelf life of catfish sticks and their effect on taste, color, texture and odor.